Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00520-005-0879-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of testicular cancer survivors and the relationship with sociodemographics, cancer-related variables, and life events

Abstract: Quality of life of testicular cancer survivors and the relationship with sociodemographics, cancer-related variables, and life events

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 31 publications
3
33
0
3
Order By: Relevance
“…49 Dahl et al 14 reported that neurotoxic adverse effects, anxiety/depression, and musculoskeletal issues were associated with poor quality of life. Fleer et al 50 found that chronic disease was also a quality-of-life correlate, although an association with number of conditions was not evaluated.…”
Section: Ahos and Self-reported Healthmentioning
confidence: 99%
“…49 Dahl et al 14 reported that neurotoxic adverse effects, anxiety/depression, and musculoskeletal issues were associated with poor quality of life. Fleer et al 50 found that chronic disease was also a quality-of-life correlate, although an association with number of conditions was not evaluated.…”
Section: Ahos and Self-reported Healthmentioning
confidence: 99%
“…Most studies indicate that overall health-related quality of life (QOL) is similar among testis cancer survivors and the general population [1][2][3][4][5][6][7][8][9]. Although QOL clearly deteriorates at the time of diagnosis and during treatment, it subsequently returns to normal levels, as defined by matched controls or the general age-matched population.…”
mentioning
confidence: 96%
“…Limited evidence suggests that although treatment is associated with a significantly increased risk of certain treatment-related side-effects (eg, fertility, neurotoxicity, and Raynaud's phenomena), 10,12 post-treatment overall quality of life may not be adversely affected by treatment approach. [13][14][15][16][17] In addition, the few prospective studies that have been published suggest that although quality of life is adversely affected during adjuvant chemotherapy and radiation therapy, levels tend to return to baseline after the completion of treatment. 16,18,19 However, several reports suggest that survivors are more likely to experience some adverse outcomes, such as anxiety, 20 chronic fatigue, 21 and sexual dysfunction.…”
mentioning
confidence: 99%